Nature, Causes And Management Of Conflict Between Federal University Oye-Ekiti Students And The Host Community, Oye-Ekiti - Agbegbedia, Anthony; Daramola, Glory Abisola (ARRUS Journal of Social Sciences and Humanities, 2024)
This study examined the nature, causes and management of the conflict between students of Federal University Oye-Ekiti and the host community Oye-Ekiti, and also evaluated the various conflict management strategies adopted for resolving the conflict. The phenomenon of conflict between students of higher institutions and their host communities is becoming rampant in Nigeria. Little emphasis is also placed on the various strategies used in managing the conflict. Both primary and secondary means of data collection were adopted for the study. The secondary source included published books, journals and online materials while the primary source involved the use of structured questionnaire administered randomly to hundred (100) respondents which were retrieved and analysed through the use of descriptive method. Findings revealed that economic deprivation, excessive exploitation of students by host communities and disrespect of students for traditions and laws in the society are triggers of the conflict. Various conflict management strategies such as mediation, negotiation and conciliation were adopted in the resolution of the conflict which were effective and binding on the two parties. The conflict affects the education of the students and also hinders the development of the community. Both parties should strive to accommodate each other in the community.